Skupinska počivališča malih uharic Asio otus v Pomurju - Katalinič, Dane (Acrocephalus, 2000)
In the winter of 1998-99, the author systematically searched for the resting places of the Long-eared Owl Asio otus in some 900 km2 large area in the Prekmurje region (NE Slovenia). Eight resting places were frequented by 108 individuals.
Keywords: bird; Birds; ptice; Ecosystem; ornitologija; Behavior, animal; sove; Seasons; Pomurje